2002
DOI: 10.1074/jbc.m107995200
|View full text |Cite
|
Sign up to set email alerts
|

Defects of the Heart, Eye, and Megakaryocytes in Peroxisome Proliferator Activator Receptor-binding Protein (PBP) Null Embryos Implicate GATA Family of Transcription Factors

Abstract: Peroxisome proliferator activator receptor (PPAR)-binding protein (PBP) is an important coactivator forPPAR␥ and other nuclear receptors. It has been identified as an integral component of a multiprotein thyroid hormone receptor-associated protein/vitamin D 3 receptor-interacting protein/activator-recruited cofactor complexes required for transcriptional activity. Here, we show that PBP is critical for the development of placenta and for the normal embryonic development of the heart, eye, vascular, and hematop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
109
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 61 publications
10
109
0
Order By: Relevance
“…In the present study, we showed that Mediator subunit Med1 is essential for erythroid development and correct induction of β-globin gene expression. As shown previously by others and us, Med1 is an important coactivator for the master regulator GATA-1 (9,10,28). Whereas other GATA factors have been shown to be essential for T-cell development (GATA-3) or hematopoietic stem cells (GATA-2) (as reviewed in ref.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, we showed that Mediator subunit Med1 is essential for erythroid development and correct induction of β-globin gene expression. As shown previously by others and us, Med1 is an important coactivator for the master regulator GATA-1 (9,10,28). Whereas other GATA factors have been shown to be essential for T-cell development (GATA-3) or hematopoietic stem cells (GATA-2) (as reviewed in ref.…”
Section: Discussionmentioning
confidence: 92%
“…The Mediator protein complex regulates transcription from specific gene enhancers in response to hormones and other extracellular signals. Deletion of its constituent subunits leads to loss of a number of transcriptional events that participate in cell division, differentiation, and metabolism (21,(35)(36)(37). We have shown that Med1 dynamically and directly associates with C/EBP-␤.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have shown that the N-terminal region of Med1 plays a critical role in mediating its interactions with other transcription factors, such as GATA1, GATA2, and Pit (21,39). Although the exact contact sites for these transcription factors in the Med1 protein have not been finely mapped, a broad region of Med1 consisting of residues 622-701 appears to form a critical binding domain (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Med1 deficiency leads to death at embryonic day 11.5. Although Med1 is not required for cell division, Med1 is critical for embryonic development of placental and cardiac development (10,14,16).…”
mentioning
confidence: 99%